Ethnopharmacological Use of Several Plants from Cipicung Village, Garut Regency, West Java Province - Amalia, Nur; Meidinata, Dita (Fakultas Kewirausahaan Universitas Garut, 2024)
Cipicung Village is an area in Garut Regency that grows a lot of medicinal plants which are used by the people as medicine. Information on the use of plants by the community has been passed down from generation to generation and so that this information is not lost, a plant inventory must be carried out. The aim of this community service activity is to determine the ethnopharmacological use of medicinal plants and document the types of plants used by the Cipicung Village community. The method used in this activity is conducting field surveys and permits, then community service activities by means of exploratory surveys regarding the value of knowledge and use of medicinal plants, as well as evaluating the results. The survey results show that the people of Cipicung Village have good knowledge and use of medicinal plants by using medicinal plants around their environment which are processed into medicinal concoctions. In Cipicung village there are 17 types of medicinal plants used by the community.